Russia reinvents its railroad. - Upson, S. (IEEE spectrum)
It's no exaggeration that the backbone of the Russian Federation is its railways. With 85,500 kilometers of track and 664,600 railcars transporting people and goods across 11 time zones, Russian Railways is practically a force of nature. In an effort to catapult its operations into the 21st century, Russian Railways has struck a technical partnership with the U.S. computer giant IBM, based in Armonk, N.Y. With IBM's help, the railway is at last overhauling the hardware, software infrastructure, and communications architecture that underpin its operations.